If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13 + a) + 13 = 0 Remove parenthesis around (13 + a) 13 + a + 13 = 0 Reorder the terms: 13 + 13 + a = 0 Combine like terms: 13 + 13 = 26 26 + a = 0 Solving 26 + a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + a = 0 + -26 Combine like terms: 26 + -26 = 0 0 + a = 0 + -26 a = 0 + -26 Combine like terms: 0 + -26 = -26 a = -26 Simplifying a = -26
| 0.80x+0.55(80)=0.40(100) | | y-12y= | | 12=m+2 | | 5(6x+35)+7(x+1)=u | | -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 | | x=4+-3y | | x^2-18+77= | | 4(2x+-1)=27+3(2x-5) | | x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 | | v^2-6v+15= | | 0=-16t^2+35t+8 | | 1-5x^2=-3x |